Hesperetin protects hippocampal neurons from the neurotoxicity of Aflatoxin B1 in mice - Chao Song; Zixu Wang; Jing Cao; Yulan Dong; Yaoxing Chen (Ecotoxicology and Environmental Safety, 2024)
Aflatoxin B1 (AFB1) is a major food and feed pollutant that endangers public health. Previous studies have shown that exposure to AFB1 causes neurotoxicity in the body. However, the mechanism of neurotoxicity caused by AFB1 is not well understood, and finding a workable and practical method to safeguard animals from AFB1 toxicity is essential. This study confirmed that AFB1 caused endoplasmic reticulum stress (ER stress) and apoptosis in hippocampal neurons using C57BL/6 J mice and HT22 cells as models. In vitro experiments showed that the aryl hydrocarbon receptor (AHR) plays a significant role in the cytotoxicity of AFB1. Finally, we assessed how hesperetin protecting against the neurotoxicity caused by AFB1. Our findings demonstrated that AFB1 increased the levels of BAX and Cleaved-Caspase3 proteins, while decreasing the levels of BCL2 protein in the CA1 and CA3 regions of the hippocampus. The AFB1 increased the expression of AHR and activated nuclear translocation. It also elevated the expression levels of Chop, GRP78, p-IRE1/ Xbp1s, and p-PERK/p-EIF2a. Importantly, we also discovered for the first time that blocking AHR in HT22 cells dramatically reduced the level of ER stress and apoptosis caused by AFB1. In vivo and in vitro studies, supplementation of hesperetin effectively reversed AFB1-induced cytotoxicity. We have demonstrated that hesperetin effectively restored the imbalance in the GSH/GST system in HT22 cells treated with AFB1. Furthermore, we observed that elevated GSH levels facilitated the formation of AFB1-GSH complexes, which enhanced the excretion of AFB1. Therefore, hesperetin improves ER stress-induced apoptosis by reducing AFB1 activation of AHR.